Low‐frequency quantitative ultrasound imaging of cell death in vivo. Issue 8 (11th July 2013) - Sadeghi‐Naini, Ali; Papanicolau, Naum; Falou, Omar; Tadayyon, Hadi; Lee, Justin; Zubovits, Judit; Sadeghian, Alireza; Karshafian, Raffi; Al‐Mahrouki, Azza; Giles, Anoja; Kolios, Michael C.; Czarnota, Gregory J.
Abstract : Purpose: : Currently, no clinical imaging modality is used routinely to assess tumor response to cancer therapies within hours to days of the delivery of treatment. Here, the authors demonstrate the efficacy of ultrasound at a clinically relevant frequency to quantitatively detect changes in tumors in response to cancer therapies using preclinical mouse models. Methods: : Conventional low‐frequency and corresponding high‐frequency ultrasound (ranging from 4 to 28 MHz) were used along with quantitative spectroscopic and signal envelope statistical analyses on data obtained from xenograft tumors treated with chemotherapy, x‐ray radiation, as well as a novel vascular targeting microbubble therapy. Results: : Ultrasound‐based spectroscopic biomarkers indicated significant changes in cell‐death associated parameters in responsive tumors. Specifically changes in the midband fit, spectral slope, and 0‐MHz intercept biomarkers were investigated for different types of treatment and demonstrated cell‐death related changes. The midband fit and 0‐MHz intercept biomarker derived from low‐frequency data demonstrated increases ranging approximately from 0 to 6 dBr and 0 to 8 dBr, respectively, depending on treatments administrated. These data paralleled results observed for high‐frequency ultrasound data. Statistical analysis of ultrasound signal envelope was performed as an alternative method to obtain histogram‐based biomarkers and provided confirmatory results. Histological analysis of tumor specimens indicated up to 61% cell death present in the tumors depending on treatments administered, consistent with quantitative ultrasound findings indicating cell death. Ultrasound‐based spectroscopic biomarkers demonstrated a good correlation with histological morphological findings indicative of cell death ( r 2 = 0.71, 0.82; p < 0.001). Conclusions: : In summary, the results provide preclinical evidence, for the first time, that quantitative ultrasound used at a clinically relevant frequency, in addition to high‐frequency ultrasound, can detect tissue changes associated with cell death in vivo in response to cancer treatments.